2023
DOI: 10.1590/1519-6984.242536
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and screening of chromium resistant bacteria from industrial waste for bioremediation purposes

Abstract: Chromium (VI) a highly toxic metal, a major constituent of industrial waste. It is continuously release in soil and water, causes environmental and health related issues, which is increasing public concern in developing countries like Pakistan. The basic aim of this study was isolation and screening of chromium resistant bacteria from industrial waste collected from Korangi and Lyari, Karachi (24˚52ʹ46.0ʺN 66˚59ʹ25.7ʺE and 24˚48ʹ37.5ʺN 67˚06ʹ52.6ʺE). Among total of 53 isolated strains, seven bacterial strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Considering that the soils evaluated are native Cerrado, whose characteristic is low fertility, with high values of attributes linked to acidity and aluminum, and low in basic cations and phosphorus (Amorim et al, 2020), thus we can justify the contrasting result between the mentioned chemical attributes and iBt, since there is a need for an adequate pH and nutrient concentrations for a satisfactory development of microorganisms (Medhi et al, 2017), including Bt, as reported in Rabinovitch et al (2017). Furthermore, for a good conditions for bacterial growth includ temperature and pH, so in low value of pH, that represent high levels of H+Al and Al in soils of Cerrado could be explain the results founded (Kalsoom et al, 2023).…”
Section: Discussionmentioning
confidence: 69%
“…Considering that the soils evaluated are native Cerrado, whose characteristic is low fertility, with high values of attributes linked to acidity and aluminum, and low in basic cations and phosphorus (Amorim et al, 2020), thus we can justify the contrasting result between the mentioned chemical attributes and iBt, since there is a need for an adequate pH and nutrient concentrations for a satisfactory development of microorganisms (Medhi et al, 2017), including Bt, as reported in Rabinovitch et al (2017). Furthermore, for a good conditions for bacterial growth includ temperature and pH, so in low value of pH, that represent high levels of H+Al and Al in soils of Cerrado could be explain the results founded (Kalsoom et al, 2023).…”
Section: Discussionmentioning
confidence: 69%
“…In this analysis, only two of the twenty bacterial strains from the river sample were able to grow in the presence of Cu and Pb at a concentration of 100 mg/L and were chosen for the subsequent experiment. The selected bacterial strains were chosen and characterized in accordance with similarities to those listed in Bergey's Manual of Determinative Bacteriology using common morphological and physiological traits [48], [49].…”
Section: Screening and Selection Of Cu And Pb Tolerant Bacterial Strainsmentioning
confidence: 99%
“…In the study of 20 bacterial strains from the zebrafish gut microbiome, only 3 strains were able to grow in the presence of zinc at a concentration of 100 mg/L (FG01, FGO2, and FG03) and were selected for the later experiment. Using common morphological, and physiological, the chosen bacterial strains were selected and described based on similarities to those listed in Bergey's Manual of Determinative Bacteriology [30], [31].…”
Section: Screening and Selection Of Zinc-tolerant Bacterial Strainsmentioning
confidence: 99%